Influence of pre-stenting on RIRS outcomes. Inferences from patients of the Global Multicentre Flexible Ureteroscopy Outcome Registry (FLEXOR) - (:unkn) unknown (My University, 2023)
BACKGROUND: Retrograde Intrarenal Surgery (RIRS) is recommended as an alternative to percutaneous nephrolithotomy for stones up to 2 cm. Pre-stenting before RIRS remains controversial with various studies differing in outcomes and recommendations. We aim to understand how pre-stenting influences surgical outcomes. METHODS: A number of 6579 patients from the TOWER group registry were divided into pre-stented (group 1) and non-pre-stented groups (group 2). Patients aged ≥18 years old, with normal calyceal anatomy were enrolled. Patients with ureteric stones, anomalous kidneys, bilateral stones, planned for ECIRS were excluded. RESULTS: Patients are homogeneously distributed in both groups (3112 vs. 3467). The predominant indication for pre-stenting was symptom relief. Overall stone size was comparable, whilst group 1 had a significantly more multiple (1419 vs. 1283, P<0.001) and lower-pole (LP) stones (1503 vs. 1411, P<0.001). The mean operative time for group 2 was significantly longer (68.17 vs. 58.92, P<0.001). Stone size, LP stones, age, recurrence and multiple stones are contributing factors for residual fragments at the multivariable analysis. The incidence of postoperative day 1 fever and sepsis was significantly higher in group 2, indicating that pre-stenting is associated with a lower risk of post-RIRS infection and a lower overall complications rate (13.62% vs. 15.89%) (P<0.001). CONCLUSIONS: RIRS without pre-stenting can be considered safe without significant morbidity. Multiple, lower-pole and large stone is a significant contributor towards residual fragments. Patients who were not pre-stented had significantly higher but low-grade complications, especially for lower pole and large volume stones. While we do not advocate routine pre-stenting, a tailored approach for these patients should include proper counselling regarding pre-stenting.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology